Two new mutations of the P5'N-1 gene found in Italian patients with hereditary hemolytic anemia: the molecular basis of the red cell enzyme disorder. - Chiarelli, L; Fermo, E; Abrusci, P; Bianchi, P; Dellacasa, C; Galizzi, A; Zanella, A; Valentini, G (2006)
Inherited pyrimidine 5'-nucleotidase type-1 (P5'N-1) deficiency is the most frequent abnormality of red cell nucleotide metabolism causing non-spherocytic hemolytic anemia. We describe two novel mutations in two Italian patients affected by P5'N-1 deficiency. One mutation is a two base deletion that occurs at the splice site junction between intron 7 and exon 8 (c.396-397del AG); the second is an in-frame deletion of three adjacent bases (c.427-429del CAA), leading to deletion of glutamine 143. The kinetic properties of Q143del variant were not grossly altered, but the variant was very heat unstable even at physiological temperatures.